Phytochemical and antibacterial properties of root extracts from Portulaca oleracea Linn. (Purslane) utilised in the management of diseases in Nigeria - Emmanuel O. Ojah; Emmanuel O. Oladele; Philip Chukwuemeka (Journal of Medicinal Plants for Economic Development, 2021)
Background: Bacteria as etiological agents have been reported to cause many diseases and have increased the rate of mortality globally. Their resistance to conventional medicine has made medicinal plants a credible alternative in the management of diseases caused by bacterial infection. In the recent times many research efforts have been directed towards the exploration of phytoconstituents with antibacterial potentials. Medicinal plants are widely used as antibacterial agents because of their high therapeutic performance, low toxicity, and affordability.